2024
DOI: 10.3390/su16051717
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management Strategies for Fruit Processing Byproducts for Biorefineries: A Review

Alfred Błaszczyk,
Sylwia Sady,
Bogdan Pachołek
et al.

Abstract: The fruit processing industry generates enormous amounts of byproducts, which are primarily removed through landfill or incineration. However, these processes cause carbon dioxide and methane emissions and release dioxin into the environment. The management of fruit processing byproducts is important for reducing the amount of food waste that is sent to landfills and for developing strategies through the reuse of these products for valorization and economic added value. Fruit processing byproducts are rich sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…Therefore, the reuse of these byproducts can lead to both economic and ecological benefits. Activities related to reduction, recycling, and reuse are part of the global trend associated with the concepts of sustainable development and consumption [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reuse of these byproducts can lead to both economic and ecological benefits. Activities related to reduction, recycling, and reuse are part of the global trend associated with the concepts of sustainable development and consumption [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This transformative approach advocates for the optimization of resources through closed-loop systems, wherein products and materials are reused, recycled, and repurposed to minimize waste and environmental impact. The management of waste is an essential component in addressing the impact on the environment and it is something that a variety of industries can be involved in [4][5][6][7]. Albania, amidst its journey toward European Union integration, has emerged as a proactive participant in this transition, spearheading initiatives aimed at embracing the circular economy ethos [8].…”
Section: Introductionmentioning
confidence: 99%
“…Managing these waste products is a significant issue in the food processing industry. The global fruit processing industry generates over 190 million tons of waste annually (Błaszczyk et al, 2024). Numerous studies have shown that fruit pulp is a valuable source of many nutritious substances.…”
Section: Introductionmentioning
confidence: 99%